야간 조명 하 안대와 소등의 수면에 대한 효과 비교 - 신주용(Juyong Shin); 임경옥(Kyoung-Ok Lim); 조성남(Seongnam Cho); 장소영(Soyeong Jang); 차승민(Seung-Min Cha); 한송이(Songy (Sumyŏn--chŏngsin saengni, 2021)
Objectives: The purpose of this study is to investigate the difference in the effects of eye-mask and light-off on sleep status according to a commercial fitness tracker and a sleep diary of psychiatric in-patients in correctional facilities where nocturnal light is compulsory. Methods: This study was conducted over 3 consecutive nights. In-patients of the National Forensic Psychiatric Hospital (n = 29) were assigned random subject numbers and slept as usual in the light-on condition on the first night. The subjects slept with eye-masks in the light-on condition on another night and without an eye-mask in the light-off condition on the other night. Subjects were asked to sleep wearing a commercial fitness tracker and to keep a sleep diary. The order of these changes in bedroom lighting condition on the second and third nights was assigned randomly to participants. Results: In comparison of the sleep variables between the light-on condition and the eye-mask condition, the Wakefullness After Sleep Onset (WASO) was shorter and sleep satisfaction was higher in the latter.(respectively, Z = 3.66, p < 0.017 ; Z = 2.69, p < 0.017) In comparison of the sleep variables between the light-on and light-off conditions, the WASO was shorter and sleep efficiency and sleep satisfaction were higher in the latter (respectively, Z = 2.40, p < 0.017 ; Z = 3.02, p < 0.017 ; Z = 3.88, p < 0.017). However, there were no differences in the sleep variables between the eye-mask condition and the light-off condition. Conclusion: Subjective improvements in sleep variables were noted in sleep diaries of institutionalized psychiatric patients under either the 'eye-mask' or 'light-off' condition. However, there were no significant differences between the 'eye-mask' and 'light-off' conditions. Therefore, we suggest that psychiatric patients in correctional facilities use eye-masks when sleeping. 목 적 : 본 연구의 목적은 침실에서 야간 조명이 강제적으로 사용되는 교정기관 내 정신과적 입원 환자들에게 상업용 활동 추적기와 수면일지를 통해 안대 착용과 완전 소등이 수면 상태에 주는 효과들의 차이를 조사하는 것이다. 방 법 : 본 연구는 3일 연속 밤 동안 수행되었다. 국립법무병원에 입원된 29명의 정신질환자들에게 무작위 연구 번호가 배정되었으며, 첫 날에는 야간 조명 환경에서 평소처럼 취침했다. 29명 연구대상자들은 다른 날에는 야간 조명환경에서 안대를 착용한 채 취침하였으며, 또 다른 날에는 완전 소등 환경에서 안대 없이 취침하였다. 29명 연구대상자들은 상업용 활동 추적기를 착용하면서 취침하도록 요청되었으며, 다음 날 아침 수면일지를 작성하였다. 연구대상자들은 이러한 둘째 밤과 셋째 밤의 침실 조도 환경 변화를 무작위로 겪도록 배정되었다. 결 과 : 조명 하 수면 환경과 안대 착용 수면 환경 비교 시, 안대 착용 수면 환경에서 수면 후 각성 시간이 짧았고, 수면 만족도가 높았다(각각, Z = 3.66, p < 0.017 ; Z = 2.69, p < 0.017). 또한, 조명 하 수면 조건과 소등 하 수면 조건 비교 시, 소등 하 수면 조건에서 수면 후 각성 시간이 짧았고, 수면 효율, 수면 만족도가 높았다(각각, 31.14분 대 15.00분, Z = 2.40, p < 0.017 ; 79.40% 대 88.10%, Z = 3.02, p < 0.017 ; 2.97점 대 4.10점, Z = 3.88, p < 0.017). 그러나 안대 착용 수면과 소등 하 수면 비교에서는 유의미한 차이가 없었다. 결 론 : 본 연구 결과 정신질환자나 교정기관의 수용자에게 수면을 개선시키기 위해 완전 소등 또는 환경 개선이 불가능할 경우에는 안대 착용을 권장하는 것이 주관적인 수면의 질과 만족도를 높이는데 유용한 방법이 될 수도 있겠다.